Mandibular Magnet Retained Complete Overdenture - Chumaidi, Glady; Dahlan, Agus; Laksono, Harry (Indonesian Journal of Dental Medicine, 2018)
Background: Complete denture in the lower jaw often has problems. The entire loss of the mandibular teeth often has a large resorption, so it is difficult to obtain retention and stability. Purpose: To report mandibular  magnet retained complete overdenture is can increase retention and stability in the lower jaw. Case: A 60-year-old man came to the Prosthodontics Clinic of RSGM Airlangga University with complaints of the old complete denture that made by previous dentist, is often unstable while talking and chewing, so the patient feel uncomfortable. The denture has been used for approximately four years. Therefore the patient wants to make a new complete denture. Case Management: PFM crown removed and 31,32,33,41,43 are treated with root canal treatment. Magnet keepers are fabricated on teeth 33,43, and metal copings are fabricated on teeth 31,32,41. The complete lower denture is attached to the magnet. Acrylic material denture are chosen. Discussion: Overdenture is a complete or partial denture that is placed above the tooth structure or the root of the original tooth which is the support of the denture. Overdenture treatment can maintain ridge height, reduced load of supporting elements, and avoid mucosal irritation. It's necessary to add retention in the form of magnets to the teeth 33 and 43 to get good retention and stability. Conclusion: Mandibular  magnet retained complete overdenture is can increase retention and stability in the lower jaw so that the patient feels satisfied and comfortable because the dentures are more retentive and stable.